Organ Specific Proteomic Dissection of Selaginella bryopteris Undergoing Dehydration and Rehydration - Deeba, Farah; Pandey, Ashutosh K.; Pandey, Vivek (Frontiers in Plant Science, 2016)
To explore molecular mechanisms underlying the physiological response of Selaginella bryopteris, a comprehensive proteome analysis was carried out in roots and fronds undergoing dehydration and rehydration. Plants were dehydrated for 7 days followed by 2 h and 24 h of rehydration. In roots out of 59 identified spots, 58 protein spots were found to be up-regulated during dehydration stress. The identified proteins were related to signaling, stress and defense, protein and nucleotide metabolism, carbohydrate and energy metabolism, storage and epigenetic control. Most of these proteins remained up-regulated on first rehydration, suggesting their role in recovery phase also. Among the 90 identified proteins in fronds, about 49% proteins were up-regulated during dehydration stress. Large number of ROS scavenging proteins was enhanced on dehydration. Many other proteins involved in energy, protein turnover and nucleotide metabolism, epigenetic control were also highly upregulated. Many photosynthesis related proteins were upregulated during stress. This would have helped plant to recover rapidly on rehydration. This study provides a comprehensive picture of different cellular responses elucidated by the proteome changes during dehydration and rehydration in roots and fronds as expected from a well-choreographed response from a resurrection plant.